Resistant Chorea Successfully Treated With Intravenous Immunoglobulin: A Case Report* - Ahmet Sami Guven; Mehmet Burhan Oflaz; Ali Kaya; Fatih Bolat; Utku Aygüneş; Füsun Dilara İçağasıoğlu (Galenos Publishing House, 2021)
Sydenham's chorea (SC) is common cause of acquired chorea in childhood. SC occurs mainly in children with untreated streptococcal infections. An effective list of therapeutic options has been used to treat this disorder: antiepileptic drugs (valproic acid, carbamazepine etc.), haloperidol, chlorpromazine, amphetamines, steroids, plasma exchange and intravenous immunoglobulins (IVIG). We report a 12-year-old girl with carditis and severely generalized chorea and successfully treated with IVIG. This case report shows that IVIG is an effective treatment for the chorea cases resistant to anticonvulsants, dopamine antagonists and steroids, although larger studies are needed to confirm this conclusion.